Efficacy of topical morphine mouthwash for chemotherapy-induced oral mucositis pain: a systematic review - Valente, Julie Azevedo Araújo; Siqueira, Barbara Caroline Silva de; Barreto, Luciana Tedgue (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Oral mucositis is a frequent and painful complication of cancer treatment, particularly in patients receiving chemotherapy and/or radiotherapy for head and neck tumors. The resulting pain can impair oral intake, communication, and treatment adherence. Topical morphine mouthwash has emerged as a potential strategy for localized pain relief, potentially reducing systemic opioid requirements. The objective of this study was to evaluate the effectiveness and safety of topical morphine mouthwash in managing mucositis-related pain in cancer patients, based on a systematic review of randomized controlled trials, with meta-analysis when feasible. This review followed PRISMA 2020 guidelines. PubMed, Embase, and Cochrane Library were searched through April 2025 for randomized controlled trials comparing topical morphine mouthwash to placebo or non-opioid oral solutions. Data were extracted independently by two reviewers, and risk of bias was assessed using the Cochrane RoB 2 tool. The primary outcome was pain intensity, and secondary outcomes included time to first systemic opioid administration and adverse events. Four randomized controlled trials involving 81 adult cancer patients were included. All trials reported that morphine mouthwash significantly reduced pain scores and, in some cases, delayed the use of intravenous opioids compared to control. No serious adverse events related to topical morphine were observed. Meta-analysis confirmed a statistically significant reduction in pain intensity favoring the intervention group (pooled standardized mean differences = -1.12; 95% confidence interval -1.85 to -0.39; p = 0.003). Morphine mouthwash appears to be a safe and effective option for managing oral mucositis pain in cancer patients. These findings support its clinical use as a localized pain control strategy. Larger and standardized randomized controlled trials are warranted to confirm efficacy and safety.